Complement fragments are biomarkers of antibody-mediated endothelial injury. (February 2020) - Stites, Erik; Renner, Brandon; Laskowski, Jennifer; Le Quintrec, Moglie; You, Zhiying; Freed, Brian; Cooper, James; Jalal, Diana; Thurman, Joshua M.
Highlights: Complement activation on endothelial cells generates complement fragments. Complement activation on endothelial cells generates microvesicles. Complement fragments are increased in antibody-mediated rejection. Plasma endothelial microparticles decreased in antibody-mediated rejection. Abstract: Antibody-mediated rejection (AbMR) adversely affects long-term graft survival in kidney transplantation. Currently, the diagnosis of AbMR requires a kidney biopsy, and detection of complement C4d deposition in the allograft is one of the diagnostic criteria. Complement activation also generates several soluble fragments which could potentially provide non-invasive biomarkers of the process. Furthermore, microvesicles released into the plasma from injured cells can serve as biomarkers of vascular injury. To explore whether soluble complement fragments or complement fragments bound to endothelial microvesicles can be used to non-invasively detect AbMR, we developed an in vitro model in which human endothelial cells were exposed to anti-HLA antibodies and complement sufficient serum. We found that complement fragments C4a and sC5b-9 were increased in the supernatants of cells exposed to complement-sufficient serum compared to cells treated complement-deficient serum. Furthermore, complement activation on the cell surface was associated with the release of microvesicles bearing C4 and C3 fragments. We next measured these analytes in plasma from kidney transplant recipients with biopsy-proven acute AbMR (n = 9) and compared the results with those from transplant recipients who also had impaired allograft function but who did not have AbMR (n = 30). Consistent with the in vitro results, complement fragments C4a and Ba were increased in plasma from patients with AbMR compared to control subjects (P < 0.001 and P < 0.01, respectively). Endothelial microvesicle counts were not increased in patients with AbMR, however, and the number of microvesicles with C4 and C3 bound to the surface was actually lower compared to control subjects (both P < 0.05). Our results suggest that plasma complement activation fragments may be useful as non-invasive biomarkers of antibody-mediated complement activation within the allograft. Complement-opsonized endothelial microvesicles are decreased in patients with AbMR, possibly due to enhanced clearance of microvesicles opsonized with C3 and C4 fragments.